2008
DOI: 10.3748/wjg.14.3650
|View full text |Cite
|
Sign up to set email alerts
|

Partial overlap of anti-mycobacterial, and anti- Saccharomyces cerevisiae mannan antibodies in Crohn's disease

Abstract: AIM:To test whether humoral immune reaction a g a i n s t myc o b a c t e r i a m ay p l ay a ro l e i n a n t i - S a c c h a r o my c e s c e r e v i s i a e a n t i b o d i e s ( A S C A )generation in Crohn's disease (CD) and/or whether it correlates with clinical subtypes. M E T H O D S :T h e d o m i n a n t A S C A e p i t o p e w a s ASCA and anti-mycobacterial antibodies were affinity purified to assess cross-reactivities. Anti-mycobacterial IgG were induced by BCG-infection of mice. RESULTS: G N L b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Their specificity has been estimated between 75 to 85% compared to control but their sensitivity is much less and their presence may vary between subsets of patients [46], [47]. Interestingly, ASCA cross react with anti-mycobacteria response [48], [49]. However, ASCA are not specific for CD disease as they can also be detected in ACD [50], [51].…”
Section: Discussionmentioning
confidence: 99%
“…Their specificity has been estimated between 75 to 85% compared to control but their sensitivity is much less and their presence may vary between subsets of patients [46], [47]. Interestingly, ASCA cross react with anti-mycobacteria response [48], [49]. However, ASCA are not specific for CD disease as they can also be detected in ACD [50], [51].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, C albicans also express common β‐glucan epitopes similar to that of S cerevisiae , suggesting that ASCA as a diagnostic tool may not be specific enough to detect individual fungi . Various sources of microbes and receptors that express these ubiquitous epitopes might also affect ASCA affinity binding, including mycobacteria M paratuberculosis and the fimH receptor on GP2 on M cells, all of which likely contain the mannose alpha 1,3 mannose epitope for ASCA . When serological markers are considered individually, ASCA has the best combined sensitivity and specificity for CD; and pANCA for UC.…”
Section: Impact Of Fungal Alterations On Ibd Diagnosis and Disease Acmentioning
confidence: 99%
“…Decreased in faeces of mice with colitis; Daily supplementation increases purine metabolism and exacerbate colitis Decreased in faeces and mucosa of IBD and during IBD flare, increased in faeces of healthy individuals and IBD in remission 30,99 Dioszegia genus Unknown Increased in the inflamed mucosa of IBD 22,33 Leptosphaeria genus Unknown Decreased in the non-inflamed mucosa of IBD 22,33 Trichosporon genus Increased in mice with colitis Decreased in non-inflamed mucosa of IBD 22,33 Filobasidium uniguttulatum Unknown Increased in non-inflamed mucosa of IBD 22,33 Xylariales genus Unknown Increased in inflamed mucosa of CD 22,33 receptor on GP2 on M cells, all of which likely contain the mannose alpha 1,3 mannose epitope for ASCA. [44][45][46][47] When serological markers are considered individually, ASCA has the best combined sensitivity and specificity for CD; and pANCA for UC. It has been demonstrated that these two antibodies in combination are more accurate in differentiating CD from UC than when used in isolation.…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%
“…Previous studies had only validated ASCA and ANCA as serological markers specifically associated with CD and UC, respectively, and had shown that a combination of the two tests could be helpful in diagnosing IBD [22][23][24][25]. Few studies have assessed ASCA and anti-MAP in patients with CD [37,38]. Thus, for the first time, anti-MAP, ASCA and ANCA profiles were analysed concomitantly in an IBD population and the usefulness of the three combined markers was demonstrated in terms of differentiating CD from UC.…”
Section: Discussionmentioning
confidence: 99%